Ensino de geografia para estudantes surdos: concepções e práticas pedagógicas - Pena, Fernanda Santos (2012)
Since the year 1992, in Uberlândia city has offered a specialized care for deaf students in mainstream education. Historically, this concern was not always present in the school. Despite the advances made, after two decades of experience, no one knows for sure if the health professionals in this network are adequately trained and if these students are indeed included. With regard to the teaching of Geography, studies and surveys are still incomplete. In this sense, this paper aims to analyze the teaching of Geography to deaf elementary school students (6th to 9th grade) in public schools in Uberlândia / MG. Met up the process of inclusion of these students and identified the concepts and pedagogical practices of teachers of Geography, Teacher Support Services Educational Specialist (ESA) and interpreters Libras. We used a qualitative research through two kinds of data collection: a semi-structured interview and observation. We sought to know, in particular, the training of professionals who work with deaf students, methodologies and teaching materials Geography used, the efficiency of the visuals, the support offered to the improvement of the teaching practice of teachers of Geography, so the demands for deaf students have greater academic success. The survey found that most teachers of Geography is not qualified to teach classes for deaf students. These teachers do not make use of Libras and have full dependence of the interpreter so that there is communication with deaf students. The ratio of teachers with teachers of Geography of the ESA is also deficient. There is a need to create moments where these professionals can dialogue and build together alternatives to improve the education of deaf students. These barriers hinder the realization of significant pedagogical practices to the educational process of deaf students and also end up restricting their participation in society. It was concluded that the most urgent current demands for school inclusion of deaf students are: teacher training, including learning the Libras; rapprochement between the ESA and the teachers of the regular classroom, the constant presence of the interpreter Libras and enabled, in the classroom, just as the research and use of methodologies and teaching materials Geography significant for these students. Teaching Geography applicant must be pedagogical practices based on visualization because the visuals facilitate student learning deaf and can bridge the gap between everyday and scientific knowledge. The technological artifacts, the Internet, the concept maps, the use of images, maps and models, as well as the realization of Field Work are promising.